1987
DOI: 10.1210/jcem-64-4-686
|View full text |Cite
|
Sign up to set email alerts
|

Feminizing Testicular Leydig Cell Tumor: Hormonal Profile before and after Unilateral Orchidectomy*

Abstract: The effect of chronic hyperestrogenism on gonadal function was studied in three men who had estrogen-secreting Leydig cell tumors before unilateral orchidectomy and for 11-43 months after surgery. All three men had low plasma gonadotropin and testosterone levels and increased estradiol levels. Impairment of testicular steroidogenesis was also suggested by increased progesterone to 17-hydroxyprogesterone and 17-hydroxyprogesterone to androstenedione ratios in both spermatic venous plasma and the medium of Leydi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
6

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 23 publications
1
13
0
6
Order By: Relevance
“…Given adipose tissue is a crucial source of aromatization of testosterone, obesity should be a certain cause of hyperestrogenism. In addition, endogenous E 2 -T ratio increase is a clinical characteristic of several conditions, including chronic liver diseases, type II diabetes mellitus, hypercholesterolemia, Klinefelter syndrome, and tumors of Leydig cells or adrenal cortex (Mineur et al, 1987;Stremmel et al, 1988;Oettel, 2002). Exogenous factors that affect E 2 -T homeostasis include various environmental agents and plant estrogens, such as xenoestrogens and phytoestrogen (Oliva et al, 2002;Srilatha & Adaikan, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Given adipose tissue is a crucial source of aromatization of testosterone, obesity should be a certain cause of hyperestrogenism. In addition, endogenous E 2 -T ratio increase is a clinical characteristic of several conditions, including chronic liver diseases, type II diabetes mellitus, hypercholesterolemia, Klinefelter syndrome, and tumors of Leydig cells or adrenal cortex (Mineur et al, 1987;Stremmel et al, 1988;Oettel, 2002). Exogenous factors that affect E 2 -T homeostasis include various environmental agents and plant estrogens, such as xenoestrogens and phytoestrogen (Oliva et al, 2002;Srilatha & Adaikan, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is not surprising as previous studies have shown discrepancies of oestrogen levels at different locations with levels at spermatic veins being about 6,000 times superior compared to serum levels. [26][27][28] The higher values at testis level indicate that even the remaining leydig cells in the remaining testis are dysfunctional resulting to endocrine manifestations as seen in our patient. We don't have the capacity to measure oestrogen level at spermatic veins in our facility; hence high oestrogen level though more likely could not be confirmed.…”
Section: Discussionmentioning
confidence: 54%
“…The cell origin of TALT is debatable; adrenal cortical rest cell [15], Leydig cell. including hilus cell [16,17] and putative pluripotential cell of the hilus [18, 19J have been considered. A recent study by Clark et al [20] on in vitro steroidogenesis and receptors of testicular masses in a patient with CAH has demonstrated that the tissue of these testicular masses was of adrenal origin.…”
Section: Discussionmentioning
confidence: 99%